PENTINGNYA KESADARAN HUKUM PADA MASYARAKAT TERHADAP KEPEMILIKAN SERTIFIKAT TANAH DALAM UPAYA MENGHINDARI TIMBULNYA SENGKETA TANAH - Lestari, Anggi; Danyanthi, Ayu Putu Laksmi (Kertha Negara : Journal Ilmu Hukum, 2023)
This study aims to understand how the public’s legal awareness of the community towards land disputes to avoid land disputes.  The Indonesian state is often called a legal state that overshadows land ownership rights.  Legal certainty of land rights requires theory as a basis for analyzing government policies.  At this time land certificates are needed to avoid something that can cause problems regarding the land.  Only parties who have an interest in land can use land documents as collateral.  In this case, because there are many land cases that occur because there are differences in the definition of land boundaries, so that problems in administration become prolonged.  In this case the land certificate is a strong piece of evidence, but the government does not guarantee legal certainty.  Normative research method is the study method is used in this study.  So the problems that will be studied in this study are: What is the importance of awareness of ownership of land title certificates?, and What are the efforts and factors that hinder land dispute resolution?.